Meme gods [videorecording (DVD)] - Adams, Nate (Director); Cedric, the Entertainer, 1965-; 50 Cent (Musician); Cranston, Bryan, 1956- (Gravitas Ventures, 2025)
The documentary dives into the wild world of memes and the creators who fuel the internet's biggest viral moments. From producer Cedric the Entertainer, this documentary reveals how memes are made, remixed, and turned into million-dollar empires.